Placenta-Derived MicroRNAs in the Pathophysiology of Human Pregnancy - Xu, Peng; Ma, Yeling; Wu, Hongyu; Wang, Yan-Ling (Frontiers in Cell and Developmental Biology, 2021)
In placental mammals, reproductive success and maternal-fetal health substantially depend on a well-being placenta, the interface between the fetus and the mother. Disorders in placental cells are tightly associated with adverse pregnancy outcomes including preeclampsia, fetal growth restriction, etc. MicroRNAs (miRNAs) represent small non-coding RNAs that regulate post-transcriptional gene expression and are integral to a wide range of healthy or diseased cellular proceedings. Numerous miRNAs have been detected in human placenta and increasing evidence is revealing their important roles in regulating placental cell behaviors. Recent studies indicate that placenta-derived miRNAs can be released to the maternal circulation via encapsulating into the exosomes, and they potentially target various maternal cells to provide a hormone-like means of intercellular communication between the mother and the fetus. These placental exosome miRNAs are attracting more and more attention due to their differential expression in pregnant complications, which may provide novel biomarkers for prediction of the diseases. In this review, we briefly summarize the current knowledge and the perspectives of the placenta-derived miRNAs, especially the exosomal transfer of placental miRNAs and their pathophysiological relevance to preeclampsia. The possible exosomal-miRNA-targeted strategies for diagnosis, prognosis or therapy of preeclampsia are highlighted.